(untitled) (TAJ: Journal of Teachers Association, 2023)
This study aimed to compare the coronary angiographic characteristics of coronary artery disease in young adults (≤40 years) and older adults (>40 years). This was a retrospective analytic study. The study was conducted at the Department of Cardiology, Rajshahi Medical College Hospital. 100 patients with coronary artery disease were included in this study. Among the 100 patients, 50% were in the ≤40 years’ group (group A) and 50% were in the >40 years’ group (group B). Coronary angiographic characteristics were analyzed for each group. Coronary artery disease was present in 72% of group A and 84% of group B. In group A, single vessel disease (SVD) was the most common pattern (38%, p=0.001), while in group B, double vessel disease (DVD) (36%, p=0.043), triple vessel disease (TVD) (26%, p=0.033), and left main vessel disease (LM) (8%, p=0.035) were more prevalent. Left ventricular dysfunction with hypokinesia was observed in the majority of patients. The left anterior descending (LAD) artery was most commonly involved in both groups, primarily in the mid and proximal segments. The right coronary artery (RCA) was the next commonly affected artery, with differences in involvement site between the two groups. This study highlights that SVD is more common among young adults, whereas DVD, TVD, and LM diseases are more prevalent in older individuals. Older age groups exhibited a higher prevalence of diabetes mellitus, while smoking, dyslipidemia, and hypertension were common risk factors for coronary artery disease in both age groups. TAJ 2023; 36: No-2: 01-09